The Effect of Task Type on the Writing Accuracy of Iranian Male and Female EFL Learners - Nouri, Zahra; Rasouli, Rezvan (The linguistics journal, 2020)
This study aimed to investigate the effect of task type on the writing accuracy of Iranian male and female EFL learners. Fifty intermediate Iranian EFL learners (aged 19-26) were chosen as the participants of the study, and were assigned into two groups based on their genders (25 males & 25 females). Three different types of writing tasks including, personal descriptive, narrative and decision making tasks, were given to them, each in one session; and they were asked to write a composition of at least 100 words for each task in 30 minutes. After collecting the research data, the accuracy was estimated by calculating the percentage of error free T-units to the total number of T-units. The collected data was entered into SPSS XXVI, and withinsubjects and between-subjects repeated measures ANOVA were used to analyze the data. The results of within-subjects repeated measures ANOVA revealed higher accuracy in personal descriptive task, followed by narrative and decision making ones, respectively. The results of between-subjects repeated measures ANOVA did not show any significant differences in the writing accuracy of both male and female EFL learners in three task types. The findings of the study may have practical implications in designing and implementing of tasks in L2 classroom settings, EFL testing, and SLA research.